Microtus agrestis ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
127. Short-tailed Field Vole Microtus agrestis French: Campagnol agreste / German: Erdmaus / Spanish: Topillo agreste Other common names: Field Vole, Short-tailed Vole Taxonomy. Mus agrestis Linnaeus, 1761, Uppsala, Sweden. Microtus agrestis is in the subgenus Agricola. In most phylogenetic reconstructions, it emerged as sister species to subgenus BlanJordimys with M. afghanus, M. bucharensis, and possibly M. juldasch:. Previously included lavernedii and rozianus as subspecies; two deeply divergent phylogenetic lineages now upgrated to species level. Monotypic. Distribution. W, C & N Europe and N Asia, from the British Is and across C & E Europe (including the Carpathian Basin) and Fennoscandia to Siberia as far E as Lena River, S to NE Kazakhstan, N Mongolia, and extreme NW China (Altai and Barluk Mts in Xinjiang). Descriptive notes. Head-body 92-132 mm, tail 30-53 mm; weight 22-72.5 g. Males are, on average, heavier (weight 35-4 g) than females (32-6 g). The Short-tailed Field Vole is of average ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on pages 332-333, DOI: 10.5281/zenodo.6707142 ...